Big Nate : code red! - Peirce, Lincoln (Peirce, Lincoln. Big Nate (Comic strip), 2026)
Sixth-grade phenom Nate Wright is a force, whether on the soccer field, a master of pranks, or as the school newspaper's cartoonist, and now he's using his talents to launch a new podcast. Spring fever is in the air, both on the baseball field and school crushes, and Nate worries that the worst team name in history may hurt his mojo. Nate's friends do their best to keep him in check, but the star of Lincoln Peirce's bestselling series is determined to overcome any obstacle: surprise locker partners, a detention-happy teacher, or even cafetorium duty with Coach John. In Big Nate: Code Red, Nate and friends pull out all the stops!